Wednesday, August 15, 2018

Equations of Motions 
  • V = u + at 
  • S= (v+ u) t                                                                                                                       2  
  • S= ut + 1 at²                                                                                              2 
  • V²= a² + 2as                                                                                               
Here, 
 u = initial velocity                                                                           v=velocity                                     
  a=uniform   acceleration                                            
 s= distance travelled                                                                         t = time period                  
              
   
  •     Derivation of V =u+ at 
 We know that, a = v – u                                                                                                 t 
    or, v – u = at 
           or, v = u + at  
           If, u = 0 m/s 
Then, v = 0 + at 
         V = at 
  • ~ t [Here, a is constant]                       (proved)                                                                              
    • Derivation of S = (v + u)t                                                                                                                       2                                  
    •      V   = (v+ u)t ...........(i)  
    •           2                     
           Again,
                                           
          or, S = V . t                                           
          or,S= (v+ u)t       [  (i)   ]                                                                                                 2                                                                                                                                                                                                                           
    •  or, S = (v + u) t                                                                                                              2                                                                                                                                   
                          
  •           or, V     s                                                                                                                            t                                   
  •                                        
          or, S = V . t                                           
          or,S= (v+ u)t       [  (i)   ]                                                                                               2                                                                                                                                                                                                                           
    •  or, S = (v + u) t                                                                                                             2    
  •       (proved)  
    •                 
    • Derivation of  S = ut + 1 at²                                                                                                   2 
    We know that, 
              
      V = v+u ......................... (i)                                                                                          2
                                                                                                                            Again,V =     
                       t  
    or, S = V . t
    or, S = (v+u)t  .................(ii)
                   2                                                                                 
                                                                                                                              
    or, v = u + at................  (iii)    
    So,(ii)= S = (u + at +u)t   [(iii) v = u + at]                                                                 2                 
         ( 2u+ at)t                                                                                                  2                                                                                                                                                                                                       2u +a                                                                                                2      2                                                                                                                                                                                                         S= ut + 1 at²                                                                                                    2                                                                                                              If, u = 0 m/s 
    S=0.t 1 at²                                                                                              2       
    Or, So,S 1 at²                                                                                                 

    • Derivation of  = a² + 2as   


                   
        V = v+u ......................... (i)                                                                                           2

       __                                                                                                                          V     s   
                  t        
                          
         or, S = V . t 
         or,S= (v+ u)t   .............(ii)                                                                                                   2  
      Again, t = v-u     ......... (iii) 
                         a                                        
      S = (v+u) (v-u)  [ t = v-u     ......... (iii)
                2         a            a
                     
      or, S =v²  - u² 
                     2a
      or, v²  - u² = 2as
      or, v² = u² + 2as
      If, u = 0
      v² = 0+ 2as
      or, v² = 2as
                          
      So, v √S                               (proved)                                                                                                    

    No comments:

    Post a Comment

    Hello guys ! This is Sanjida from Science Sparkles .